BMP 2/7 Release System for Nucleus Pulposus Regeneration. Issue 1 (April 2016) - Lang, Gernot; Li, Zhen; Chen, Xu; Sacks, Hagit; Yayon, Avner; Weber, Franz; Alini, Mauro; Grad, Sibylle
Introduction: Nucleus pulposus (NP) replacement offers a novel therapy for degenerative disc disease (DDD). Previously a novel polyurethane scaffold (PUS) and a fibrinogen-hyaluronic acid (FBG-HA) conjugate based hydrogel were developed. 1, 2 The aim of this ex vivo study (EVS) was to evaluate the regenerative potential of the PUS and the FBG-HA hydrogel with/without transglutaminase (TG) crosslinked bone morphogenetic protein (BMP)-2/7 heterodimer in an organ culture system (OCS). Additionally an in vitro study (IVS) was conducted to evaluate the anabolic stimulus and biocompatibility of FBG-HA conjugate cell constructs containing different concentrations of covalently bound BMP-2/7. Material and Methods: IVS: Bovine NP cells were seeded into FBG-HA conjugate hydrogel beads at 1.2x10 5 cells per bead (4x10 6 cells/ml). Each bead was prepared by suspending 1.2x10 5 NP cells in 20µl of FBG-HA conjugate. Finally 10µl of thrombin (5.2 U/ml) containing 0, 1000, or 5000 ng/ml TG-BMP-2/7 were added ( n = 6/group). Beads were cultured for 7 or 14 days. Conditioned medium was collected for biochemical analysis. Gene expression was analyzed and DNA- and GAG content of the samples was measured. For the EVS, discoid/ravioli shape PUS were manufactured as previously described [1, 2]. Bovine IVDs with endplates were nucleotomized and refilled with either (1) PUS, (2) PUS surrounded by 50–80 µl FBG-HA or (3) PUS surrounded by 50–80µl FBG-HA containing 5000 ng/ml TG-BMP-2/7 ( n = 8/group). Empty discs served as controls. Biomaterials were evaluated in an OCS under dynamic load for 14 days at 0–0.1 MPa, 0.1 Hz for 3 hour/day. Disc height was recorded after load and recovery at day 1, 7 and 14. Disc tissue was harvested after 14 days and gene expression was analyzed. GAG and Collagen-content of the disc tissue was assessed and Proteoglycan synthesis was analyzed by Sulfur-35 ( 35 S) incorporation measurement. Histology was performed using Safranin O/Fast Green staining. One-way ANOVA was used to determine statistical significance. Results: IVS: A trend of higher Aggrecan expression in hydrogels with 5000 ng/mL of TG-BMP-2/7 was observed on day 7 compared with hydrogels without ( p = 0.065) and with 1000 ng/mL ( p = 0.067) of TG-BMP-2/7. On day 14, there was a trend of higher Collagen 2 expression in hydrogels with 5000ng/mL of TG-BMP-2/7 compared with hydrogels without ( p = 0.085) and 1000 ng/mL ( p = 0.053) of TG-BMP-2/7. GAG/DNA ratio was significantly higher in NP cell-seeded FBG-HA hydrogels containing 1000ng/ml and 5000ng/ml TG-BMP-2/7 compared with control after 7 days. EVS: All 3 implant groups maintained their disc height after dynamic load, while it dropped by 7% in empty controls ( p < 0.001 versus implant groups). When FBG-HA hydrogel containing TG-BMP-2/7 was implanted, the gene expression of Aggrecan in NP tissue increased 4.5-fold ( p = 0.083). GAG/DNA ratio increased by 46% in the remaining NP tissue when TG-BMP-2/7 was applied ( p = 0.113). Conclusion: The PUS is able to restore the disc height of nucleotomized discs; addition of FBG-HA hydrogel does not affect the swelling capacity of the PUS in situ. Due to their stimulation of anabolic gene expression and production of NP ECM components the FBG-HA hydrogel and TG-BMP2/7 may support biological repair of NP tissue. Acknowledgment: Funded by the European Commission under the FP7–NMP Project NPMimetic. Disclosures: None. References Lang G, Li Z, Chen X, et al. Biomimetic nucleus pulposus replacement for the treatment of degenerative disc disease. Global Spine J 2015;5(Suppl 1):A247 Li Z, Kaplan KM, Wertzel A, et al. Biomimetic fibrin-hyaluronan hydrogels for nucleus pulposus regeneration. Regen Med 2014;9(3):309–326